High resolution Late-glacial and early-Holocene summer air temperature records from Scotland inferred from Chironomid assemblages - Brooks, Stephen J.; Matthews, Ian P.; Birks, Hilary H.; Birks, Harry John Betteley (Quaternary Science Reviews, 2015)
Lateglacial and early-Holocene mean July air temperatures have been reconstructed, using a chironomid-based inference model, from lake-sediment sequences from Abernethy Forest, in the eastern Highlands of Scotland, and Loch Ashik, on the Isle of Skye in north-west Scotland. Chronology for Abernethy Forest was derived from radiocarbon dates of terrestrial plant macrofossils deposited in the lake sediments. Chronology for Loch Ashik was derived from tephra layers of known ages, the first age-depth model of this kind. Chironomid-inferred temperatures peak early in the Lateglacial Interstadial and then gradually decline by about 1 °C to the beginning of the Younger Dryas (YD). At Abernethy Forest, the Lateglacial Interstadial is punctuated by three centennial-scale cold oscillations which appear to be synchronous with the Greenland Interstadial events GI-1d, when temperatures at Abernethy fell by 5.9 °C, GI-1c, when temperatures fell by 2.3 °C, and GI-1b, when temperatures fell by 2.8 °C. At Loch Ashik only the oscillation correlated with GI-1d is clearly defined, when temperatures fell by 3.8 °C. The start of the YD is clearly marked at both sites when temperatures fell by 5.5 °C at Abernethy Forest and 2.8 °C at Loch Ashik. A warming trend is apparent during the late-YD at Abernethy Forest but at Loch Ashik late-YD temperatures became very cold, possibly influenced by its close proximity to the Skye ice-field. The rapidly rising temperatures at the YD – Holocene transition occur about 300 years earlier at both sites than changes in sediment lithology and loss-on-ignition. The temperature trends at both sites are broadly similar, although between-site differences may result from the influence of local factors. Similar climate trends are found at other sites in the northern British Isles. However, the British summer temperature records differ in detail from trends in the oxygen-isotope records from the Greenland ice-cores and from other chironomid-inferred temperature records available from Scandinavia, north-west ...